Predictors of metabolic syndrome among adults: a hospital based cross-sectional study - Shyam D. Thombre; Mahavir P. Nakel; Simran S. Hajare; Bharat B. Chavan (International Journal Of Community Medicine And Public Health, 2026)
Background: Metabolic syndrome (MetS) is a growing public health challenge globally, with particularly high and rising prevalence in rapidly urbanizing nations like India. Characterized by a cluster of interrelated metabolic abnormalities, MetS significantly elevates risk of type 2 diabetes mellitus and cardiovascular disease. Hospital-based prevalence data from tier-2 cities of Maharashtra remain limited. Methods: A hospital-based cross-sectional study was conducted from July to September 2025 among 381 adults (aged ≥18) at the outpatient services of a district hospital ch. Sambhajinagar. Data were collected using a WHO STEPS-based structured questionnaire. Metabolic syndrome was diagnosed by the modified NCEP ATP III criteria with Asia-specific waist circumference thresholds. Data were analysed using SPSS v29; chi-square test and multivariable binary logistic regression were applied; p